Contracting firm’s failure and financial related factors - Ab Halim, Mohd Suberi; Osman, Omar; Jaafar, Mastura (2008)

(untitled)
This paper is discussing about the role of the financial management in influencing the success of the constructing firms in the construction industry. Based on the previous studies on the impact of financial factors to the failure of the construction projects, bad financial management and lack of capital are identified to be the main determinants of the construction failure (Kangari,1998 & Noven,1996 ). Since 1988 the construction industry has experienced a higher-than-average business failure rate when compared to the failure rate of all other businesses (Dun & Bradstreet 2002 ). Large or small, old or new, domestic or foreign construction companies; they are among the statistics of failed construction companies. What are the causes of failure for the construction companies? Why construction projects could not be completed within the original schedule? Why there are so few listed successful contractors? This article provides the actual example of contractor’s failure in the construction industry world wide.